MODEL PEMBELAJARAN OSBORN UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Nurafifah, Luthfiyati; Nurlaelah, Elah; Usdiyana, Dian (Universitas Wiralodra, 2016)
The  purpose  of  this  research  is  to find out the increase of student?s mathematical problem solving competence through the implementation of Osborn Learning Model, as well as compare it with the  student  who  earned  conventional learning.    In  addition,  the  purpose  of this research is to find out the increase of mathematical  problem  solving  competence on a group of student with high, middle, and low capability. The next purpose is to find out the attitude of the students against the osborn learning model. Methods used in this research is quasi Experimenter Method with pretest and post-test Marginalized Control Design. Population on this research are all of  students  of  VIII  grades  in  SMPN  1 Bandung. Samples on this research are two classes   of   VIII   grades,   one   class   as Experimental Class and the other one as control    class.    Research    data    obtained through the test of student?s mathematical problem solving competence, questionnaire, and  observation  sheets.  The  result  of  this research shows that the increasing of student?s   mathematical   problem   solving competence with Osborn Learning Model better than   the increasing of student?s mathematical  problem  solving  competence with conventional learning. There are differences in the increasing competence on the groups of high capability, middle capability and low capability in osborn class and   conventional   class.   In   general,   the students  give  a  positive  attitude  against Osborn Learning Model.